2022
DOI: 10.1111/jace.18584
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the role of Joule heating on flash sintering using a combined experimental and modeling approach

Abstract: Flash sintering is a novel technique of ultrafast densification. There is a continuous debate over the mechanisms that are responsible for such fast sintering. In this work, we have assessed the role of Joule heating and thermal runaway on densification using a combined experimental and modeling approach. First, flash sintering (FS) experiments have been carried out for three different oxides that have very different electrical and thermal conductivities, namely, 3-and 8-mol% yttria-stabilized zirconia and tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Li et al [ 41 ] used FEM coupled with a phenomenological constitutive equation to simulate the densification of flash sintering of 3YSZ. Arya et al [ 42 ] used the master sintering curve (MSC) to include the influencing factor of the heating rate to predict the densification behavior of 3YSZ, 8YSZ, and TiO 2 . Their prediction of relative density (RD) matches closely with the experimental observation at a higher current density (100–150 mA mm − 2 ) while failing at a lower current density (<100 mA mm − 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 41 ] used FEM coupled with a phenomenological constitutive equation to simulate the densification of flash sintering of 3YSZ. Arya et al [ 42 ] used the master sintering curve (MSC) to include the influencing factor of the heating rate to predict the densification behavior of 3YSZ, 8YSZ, and TiO 2 . Their prediction of relative density (RD) matches closely with the experimental observation at a higher current density (100–150 mA mm − 2 ) while failing at a lower current density (<100 mA mm − 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] However, other studies suggested that the effect of electric field in FS and the extremely high maximum temperature of the sample also play a role in the enhanced densification. [29,30] To study the temperature profile of the ceramic sample for investigating the densification mechanisms during ECAS, modeling efforts have been made both on FS [31][32][33][34] and UHS [8,9,26,35] in recent years. Mishra et al [26] adopted finite element methods (FEM) to simulate the temperature distribution in strontium titanite (STO) during UHS and found that the temperature required to densify the ceramic green body by UHS is comparable to that by conventional sintering (CS).…”
Section: Introductionmentioning
confidence: 99%